The holiday carbon footprint in tourism education: Learning from practice and experience - Bas Amelung; Eke Eijgelaar (Investigaciones Geográficas)
Tourism is on course to thwart humanity’s efforts to reach a zero carbon economy because of its high growth rates and carbon intensity. To get out of its carbon predicament, the tourism sector needs professionals with carbon literacy and carbon capability. Providing future professionals in the full spectrum of tourism-related study programmes with the necessary knowledge and skills is essential. This article reports on ten years of experience at a BSc tourism programme with a carbon footprint exercise in which students calculate the carbon footprint of their latest holiday, compare their results with others and reflect on options to reduce emissions. Before they start, the students are provided with a handout with emission factors, a brief introduction and a sample calculation. The carbon footprints usually differ by a factor of 20 to 30 between the highest and lowest. Distance, transport mode and length of stay are almost automatically identified as the main causes, and as the main keys for drastically reducing emissions. The link to the students’ own experience makes the exercise effective, the group comparison makes it fun. As the exercise requires no prior knowledge and is suitable for almost any group size, it can be integrated into almost any tourism-related study programme.